Potential for Antibacterial Activity of Chitosan-Polyvinyl Alcohol Membrane Loaded with Green Grass Jelly Leaf and Moringa Leaf Extract as a Wound Dressing - Nur Inayatullah; Tetty Kemala; Irma Herawati Suparto (Jurnal Kimia Sains dan Aplikasi, 2022)
Chitosan is a natural polymer that can be used as wound dressing material; however, it has rigid and brittle properties. A combination of chitosan and polyvinyl alcohol (PVA) is expected to allow improvement of chitosan’s mechanical properties. Green grass jelly leaf (Cyclea barbarta M.) and moringa leaf (Moringa oleifera L.) have antibacterial compounds that can be added to the chitosan-PVA composite membrane. The purpose of the research was to develop and characterize the chitosan-PVA composite membrane with the addition of green grass jelly leaf and moringa leaf extracts to enhance the antibacterial activity of the membranes that have potential as a wound dressing. Both extracts with various composition volumes (75:25, 50:50, and 25:75) were tested for antibacterial activities against S. aureus and E. coli. Chitosan-PVA composite membrane with the volume ratios of 5:5, 6:4, and 7:3 was added with extract with the highest antibacterial activity. The composites were characterized for density, water vapor permeability, tensile strength, elongation, Fourier Transform Infrared spectroscopy, and Scanning Electron Microscope. The most significant inhibition zone was shown by an extract ratio of 50:50 against S. aureus and E. coli, 13.00±1.17 mm and 7.00±0.17 mm, respectively. Composite membrane with the addition of extract had a larger inhibition zone against S. aureus (9.75±0.75 mm) and E. coli (7.50±0.65 mm) than without extract. Chitosan-PVA(5:5)+extract membrane showed excellent density and water vapor permeability compared to other membrane ratio compositions. Mechanically, the addition of extract decreased the tensile strength and elongation of the membranes; however, it still complied with the medical material standard criteria. The characterization for functional groups showed that chitosan-PVA+extract generated the N-H group peak with two wavenumbers expressed as overlapping amides with amines and protonated amines. The SEM analysis showed that the addition of extract was not distributed homogeneously on the membrane surface.